Money in monetary policy design under uncertainty: A formal characterization of ECB-style cross-checking - Günter W. Beck; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
The European Central Bank has assigned a special role to money in its two pillar strategy and has received much criticism for this decision. The case against including money in the central bank's interest rate rule is based on a standard model of the monetary transmission process that underlies many contributions to research on monetary policy in the last two decades. In this paper, we develop a justification for including money in the interest rate rule by allowing for imperfect knowledge regarding unobservables such as potential output and equilibrium interest rates. We formulate a novel characterization of ECB-style monetary cross-checking and show that it can generate substantial stabilization benefits in the event of persistent policy misperceptions regarding potential output.
urn:nbn:de:hebis:30-43991
Keywords: E32; E41; E43; E52; E58; 330; Monetary Policy; Money; Quantity Theory; Phillips Curve; European Central Bank; Policy Under Uncertainty; Geldpolitik; Entscheidung bei Unsicherheit; Quantitätstheorie; Phillips-Kurve; Zentralbank; EU-Staaten